Legal Status and Consequences of Civil Agreements Made without a Notarial Authentic Deed - Yenny Febrianty; Nurifana Umar; Muh. Fachrur Razy Mahka; Muhammad Sabir Rahman (Lembaga Yasin AlSys, 2025)
Authentic acts performed by notaries play a crucial role in the Indonesian civil law system because they provide legal certainty and evidentiary guarantees for the parties concerned. Although notaries, as public officials, possess the legal authority to codify the intentions of the parties into lawful deeds with full evidentiary weight as stipulated in Article 1868 of the Civil Code, Indonesian civil law does not require all agreements to be formalized as authentic notarial deeds as long as they comply with the validity requirements in Article 1320 of the Civil Code. In practice, civil agreements without notarial validation are frequently made and documented as handwritten or private deeds, a practice that raises legal challenges in the event of disputes, particularly regarding the legal validity of the agreement and its evidentiary force in court. This study aims to analyze the legal status of civil agreements concluded without an authentic notarial deed and the consequent legal ramifications from the perspectives of civil law and evidentiary law. Employing normative legal research, the study uses statutory and conceptual approaches, supported by an examination of legal concepts and relevant court decisions. The findings demonstrate that a civil agreement without an authentic notarial deed remains legally valid and binding on the parties as long as it fulfills the substantive requirements for validity; however, it lacks comprehensive evidentiary strength because it does not meet the external, formal, and material standards characteristic of an authentic deed. As a result, the parties face weaker legal protection, reduced legal clarity, and a higher potential for disputes. The study concludes that the use of authentic notarial deeds is an essential instrument for preventing legal problems and ensuring legal certainty and clarity in civil relations.